Penerapan Permainan Pencocokan Warna Menggunakan Media Stik untuk Mengembangkan Motorik Halus Anak dengan Hambatan Pendengaran - Anggriani Biya; Rahma Amelia Mudiran; Tri Padrila Matulu; Pupung Puspa Ardini; Sri Depi Mustapa; Liyanti Abdul Rahman; Lisna Oktafia (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
Children with hearing impairment tend to rely on visual information during the learning process; therefore, they require concrete, attractive, and accessible learning media. This study aims to describe the implementation of a color-matching game using stick media to develop the fine motor skills of children with hearing impairment. This research employed a descriptive qualitative approach. Data were collected through observation, documentation, and developmental notes during the learning activities. The activity was carried out by introducing basic colors, demonstrating how to match colors, and guiding children to pick up, hold, move, and place colored sticks according to the provided color patterns. The findings indicate that the color-matching game using stick media supported children’s fine motor development, particularly in hand-eye coordination, finger movement accuracy, grasping skills, movement concentration, and independence in completing tasks. The children appeared more active, enthusiastic, and able to follow visual instructions during the learning process. The colorful stick media provided a concrete and enjoyable learning experience that was appropriate for the learning characteristics of children with hearing impairment. Therefore, the color-matching game using stick media can be used as an alternative learning medium to develop fine motor skills in early childhood learners with hearing impairment.